1999
DOI: 10.1002/(sici)1097-4547(19990601)56:5<547::aid-jnr10>3.0.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Potentiation of GABAA receptor-mediated Cl- current by urotensin peptides in identified Aplysia neurons

Abstract: Gamma-aminobutyric acid (GABA) is the main inhibitory neurotransmitter in the vertebrate and invertebrate central nervous systems, including those of molluscs. The effects of extracellularly applied urotensin peptides (urotensin I (UI) and urotensin II (UII)) on the GABA-induced Cl- current recorded from identified neurons (R9 and R12) of Aplysia kurodai were investigated using voltage-clamp and pressure ejection techniques. Focal application of 100 nM UI and UII potentiated the GABA-induced Cl- current withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…In contrast, UII-like sequences have not been detected in the sea lamprey (Petromyzon marinus; Decatur et al, 2013) and in nonvertebrate chordates, such as tunicates or amphioxus. The existence of a UII-like peptide was recently reported in the marine mollusc Aplysia californica (Romanova et al, 2012), and UII has been found to potentiate GABA A receptor-mediated chloride current in Aplysia neurons (Sawada and Ichinose, 1999), suggesting that UII is an ancient peptide that existed before the emergence of vertebrates. However, two observations cast doubt on this hypothesis: 1) the sequence of the Aplysia UII-like peptide is not located at the C terminus of its precursor, as for all other members of the UII/URP family; and 2) although several other protostomian species do possess an orthologous UII-like precursor gene, they are apparently devoid of UT-like gene (personal communication).…”
Section: Urotensin II and Urotensin Ii-related Peptide In Tumor Cellsmentioning
confidence: 91%
“…In contrast, UII-like sequences have not been detected in the sea lamprey (Petromyzon marinus; Decatur et al, 2013) and in nonvertebrate chordates, such as tunicates or amphioxus. The existence of a UII-like peptide was recently reported in the marine mollusc Aplysia californica (Romanova et al, 2012), and UII has been found to potentiate GABA A receptor-mediated chloride current in Aplysia neurons (Sawada and Ichinose, 1999), suggesting that UII is an ancient peptide that existed before the emergence of vertebrates. However, two observations cast doubt on this hypothesis: 1) the sequence of the Aplysia UII-like peptide is not located at the C terminus of its precursor, as for all other members of the UII/URP family; and 2) although several other protostomian species do possess an orthologous UII-like precursor gene, they are apparently devoid of UT-like gene (personal communication).…”
Section: Urotensin II and Urotensin Ii-related Peptide In Tumor Cellsmentioning
confidence: 91%
“…At the present time, information relative to the functional role of U-II in the nervous system is limited. The only study to date showed a potentiation of GABA effects in Aplysia neurons (Sawada and Ichinose 1999). In the present study, we investigated the effects of U-II on [Ca 2+ ] i homeostasis in rat spinal motoneurons and the underlying signal transduction mechanisms.…”
mentioning
confidence: 93%